2019
DOI: 10.13005/bbra/2777
|View full text |Cite
|
Sign up to set email alerts
|

Some Reproductive Biology Studies of Rabbitfish Siganus canaliculatus (Park, 1797) from the Southern Coastal Waters of Jeneponto, South Sulawesi, Indonesia

Abstract: The rabbitfish Siganus canaliculatus population has been exploited intensively in the Jeneponto Regency South Sulawesi by fishermen used non selective fishing gear, throughout the year even the spawning season. The intensive fishing without management policy can caused decreasing of the rabbit fish population, and if it continues population will be collapse. This study was conducted to investigate some of the reproductive biological study of this species. A total of 1821 specimens of S. canaliculatus consistin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The fecundity of the female S. canaliculatus population in Inner Ambon Bay is relatively high, ranging from 198,400 to 783,750 eggs. Higher than the report of Suwarni et al (2019), who obtained 5,416-130,760 eggs (range of body length (8.5-24.5 cm TL), Tharwat (2004) 58,925-838,652 eggs (17.0-35.0 cm TL), but still below Al-Marzouqi et al (2011) which obtained 242,042-607,615 eggs (26.5-37.5 cm TL). According to Effendie (2002), fecundity variations in fish are related to age composition, feed availability, population density, temperature, and dissolved oxygen.…”
Section: The Size At First Maturity and Fecunditymentioning
confidence: 56%
See 4 more Smart Citations
“…The fecundity of the female S. canaliculatus population in Inner Ambon Bay is relatively high, ranging from 198,400 to 783,750 eggs. Higher than the report of Suwarni et al (2019), who obtained 5,416-130,760 eggs (range of body length (8.5-24.5 cm TL), Tharwat (2004) 58,925-838,652 eggs (17.0-35.0 cm TL), but still below Al-Marzouqi et al (2011) which obtained 242,042-607,615 eggs (26.5-37.5 cm TL). According to Effendie (2002), fecundity variations in fish are related to age composition, feed availability, population density, temperature, and dissolved oxygen.…”
Section: The Size At First Maturity and Fecunditymentioning
confidence: 56%
“…The sex ratio of S. canaliculatus between different seagrass habitats in Inner Ambon Bay is 1.1: 1.0-2.2: 1.0 (Table 3). Differences in the sex ratio of S. canaliculatus were also found by Wassef and Hady (1997) in the Arabian Gulf (1.4: 1.0-2.3: 1.0) and Suwarni et al (2019) in the waters of Jeneponto, South Sulawesi-Indonesia (1.7: 1.0-8.2: 1.0). The results of the Chi-square test showed that the sex ratio of S. canaliculatus in Inner Ambon Bay (Table 3) was significantly different in monospecific seagrass vegetation (P > 0.01), presumably due to the capture of fish of certain sex, which was more dominant.…”
Section: The Sex Ratio Gonad Maturity Stage and Gonado Somatic Indexmentioning
confidence: 68%
See 3 more Smart Citations